2007
DOI: 10.1016/j.stem.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Phenotypic, Functional, and Molecular Topography of a Myeloerythroid Progenitor Cell Hierarchy

Abstract: The major myeloid blood cell lineages are generated from hematopoietic stem cells by differentiation through a series of increasingly committed progenitor cells. Precise characterization of intermediate progenitors is important for understanding fundamental differentiation processes and a variety of disease states, including leukemia. Here, we evaluated the functional in vitro and in vivo potentials of a range of prospectively isolated myeloid precursors with differential expression of CD150, Endoglin, and CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
703
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 594 publications
(762 citation statements)
references
References 49 publications
54
703
2
3
Order By: Relevance
“…This prompted us to analyze LSD1-kd granulomonopoiesis in more detail. Quantification of granulomonocytic progenitors (GMPs) using high-resolution cytometry 30 (Supplementary Figure S1) revealed that LSD1-kd increased GMPs by twofold above controls. We assessed myeloid progenitors, which when committed to the monocytic/dendritic cell lineage (MDP) express the M-CSF receptor (CD115).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prompted us to analyze LSD1-kd granulomonopoiesis in more detail. Quantification of granulomonocytic progenitors (GMPs) using high-resolution cytometry 30 (Supplementary Figure S1) revealed that LSD1-kd increased GMPs by twofold above controls. We assessed myeloid progenitors, which when committed to the monocytic/dendritic cell lineage (MDP) express the M-CSF receptor (CD115).…”
Section: Resultsmentioning
confidence: 99%
“…We examined nine sequential stages of erythropoiesis using a combination of previously established markers (Supplementary Figure S4A). The PreMegE (1), PreCFU-E (erythroid colony-forming unit progenitors) (2) and CFU-E (3) early erythroid progenitors were studied according to the strategy described by the Bryder group 30 (Supplementary Figure S1). To achieve high resolution in separating stages (4) through (9) of terminal erythropoiesis, we assessed c-kit 33 and CD44 34 markers along side the widely used combination of CD71 and Ter119.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed BM cells according to the cell surface marker protocol established previously for highresolution fractionation of BM progenitor compartments. 19 From lineage-depleted BM (LIN À ), we identified donor-derived GMPs (Figures 2a and b). Notably, the block in myeloid differentiation caused by biallelic Cebpa mutations occurred at the pGMP stage as shown before for the KL genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Hematopoietic stem and progenitor cells were analyzed as previously described. 19 Briefly, BM cells were stained with a cocktail of PE-Cy5 conjugated antibodies (BioLegend) against lineage markers B220, CD3, CD11b, Gr1 and Ter119. Lineage-negative (Lin À ) cells were defined as Quantitative PCR analysis (Fluidigm)…”
Section: Breeding and Fetal Liver Transplantationmentioning
confidence: 99%
“…Pellet was then treated with RBC lysis solution for 5 min. After resuspension in PBS and washing, cells were stained with lineage markers on APC (CD4, CD5, CD8, CD11b, B220 (CD45R), Gr1, Ter119, and CD41), CD117-APCCy7, Sca1-PECy7, CD16/32 PerCP5.5 (eBioscience), CD150-PE, and EndoglinPacific Blue (Biolegend) and gating as described by Pronk et al (24).…”
Section: Methodsmentioning
confidence: 99%